Prevalence and Severity of Molar Incisor Hypomineralization in a Region of Germany – A Brief Communication - Sonja E. Preusser, DDS; Verena Ferring, DDS; Carl Wleklinski, DDS; (Blackwell Synergy, 2007)
Molar incisor hypomineralization (MIH) is a developmental disturbance concerning permanent incisors and first permanent molars. The aim of this study was to ascertain the frequency of MIH in the region of central Hesse, Germany.